2019
DOI: 10.2217/rme-2019-0019
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Regeneration: A Bibliometric Analysis of the Most Influential Studies

Abstract: Aim: The aim of the present study is to identify the most influential research articles and their main characteristics in the specialty of periodontal regeneration. Materials & methods: The Web of Science database advance search was performed in the subject category of ‘Dentistry, Oral surgery and medicine’ from January 2004 to October 2018 to retrieve citations data. Results: The majority of the articles were published in journals dedicated to the specialty of periodontology. Among the top-cited articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 114 publications
0
16
0
Order By: Relevance
“…29 The United States was also the country with the largest number of papers in other bibliometric studies in different areas of dentistry. 11,12 It may result from the fact that some of the world's leading research centres are located in the United States, where more funding is invested in research. 30 The lower presence of Asia, 31,32 The choice of data source influences the analysis and the outcomes of bibliometric studies.…”
Section: Discussionmentioning
confidence: 99%
“…29 The United States was also the country with the largest number of papers in other bibliometric studies in different areas of dentistry. 11,12 It may result from the fact that some of the world's leading research centres are located in the United States, where more funding is invested in research. 30 The lower presence of Asia, 31,32 The choice of data source influences the analysis and the outcomes of bibliometric studies.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting observation was that, in comparison with the relevant present results, i.e. the papers highly cited within the period 2004-2018, the 2019 Shaikh et al [34] report included only 11 of the 18 periodontal regeneration papers listed in Table 1. Seven papers, i.e.…”
Section: Discussionmentioning
confidence: 72%
“…The H-Classic Index (HCI) is a bibliometric index, proposed by Martıńez and coworkers [33], which is sensitive to the citation practices of any research discipline. Recently, some studies using bibliometric methods have been used to investigate the literature on periodontal regeneration [24,34]. Gutiérrez-Vela et al [24] have identified a significant increase in the literature related to this field, and Shaikh et al [34] have highlighted the most influential papers for the period 2004-2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The academic scientific research has gradually increased in the last years following the world trend and today represents an important element for university academic careers in the bibliometric disciplines [4,5]. Scientometrics is the discipline that evaluates the quality of the scientific production by techniques and indicators able to measure the bibliographic data and the process of scholarly communication [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%